Großbritannien: Wird der Zugbetrieb verstaatlicht? Eine aktuelle Kurzanalyse zur Franchiseproblematik im britischen Schienenpersonenverkehr. - Merkert, Rico (DVV Media Group, 2009)
Am 1. Juli 2009 wurde in Großbritannien beschlossen, dass die National Express Group ihren Franchisevertrag für die East Coast Mainline unter der Bedingung einer Strafzahlung von 72 Mio. GBP zurückgeben muss. Daraufhin war in der deutschen Presse vielfach zu lesen, dass das britische Reformmodell nun endgültig gescheitert sei und dass nach der Verstaatlichung von Railtrack nun die Verstaatlichung des Bahnbetreibers National Express erfolge. Daher wird argumentiert, dass die Privatisierung der britischen Eisenbahn grandios gescheitert sei. Muss die Deutsche Bahn AG deshalb um ihr eigenes Franchiseunternehmen Chiltern Railways Ltd. und ihre Beteiligungen an der London Overground Rail Operations Ltd. und der Wrexham, Shropshire and Marylebone Railway Ltd. bangen? Mitnichten. Der Beitrag will auf einige wichtige Punkte hinweisen, die eine differenziertere Beurteilung der aktuellen Situation erlauben.

Following the announcement that NXEC Trains Ltd. would be striped off its East Coast Main Line franchise contract some fear (or hope) that not only National Express Group but all train operators will be re-nationalised. This paper shows that neither will happen. It also highlights, that the DfT always had very substantial control over this and all its franchises and that a more strategic approach to the cap-and-collar arrangements could have eased the current situation. It is not surprising that the business model of NXEC (the franchise that will be put under direct DfT control for some time now) did not work under the economic circumstances that train operating companies currently face in Britain. Based on an assumed annual passenger growth of 9- 10 %, NXEC was ,prepared to pay the DfT a premium of £ 1.4 Mrd. over the franchise period of 2007-2015. Whilst this model worked initially, the growth this year was limited to 0.3 %. Both sides, the DfT and NXEC could have seen this coming, but the DfT did not agree to shift its contractually built-in revenue support for such circumstances forward (normally it would have kicked-in at the end of 2011), It would have been interesting to see whether that strategy would have been a more cost efficient approach. At the end of the day the franchise will be re-let and meanwhile consultants will enjoy the assignment of preparing the line for its next private operator.
UK: Will all train operations be re-nationalised?
Keywords: Verkehr; Eisenbahn; Schienenverkehr; Verkehrsunternehmen; Privatisierung; Verstaatlichung; Eisenbahnunternehmen; Unternehmensbeteiligung